Pyotr – Letters from the Gulag - Kuiper, Jan Jaap (Netherlands : Dutch Film and Television Academy, 2008)
In 1937, Pyotr Alexeyev was arrested by Stalin's secret police and thrown into a Gulag prison camp for alleged counterrevolutionary activities. More than half a century later, Alexeyev's great-granddaughter came upon a stack of letters that he wrote to his wife in 1938. The camera follows her to the Siberian tundra where Alexeyev's camp once stood. Aside from a few nameless graves and some ruins, there are almost no signs of the horrible prison camps left. Family photos and archive footage gradually reveal a tragic family history.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films